2007
DOI: 10.1073/pnas.0705837104
|View full text |Cite
|
Sign up to set email alerts
|

Axonal transport mediates West Nile virus entry into the central nervous system and induces acute flaccid paralysis

Abstract: West Nile virus (WNV) has emerged as a significant cause of epidemic viral encephalitis and flaccid limb paralysis, yet the mechanism by which it enters the CNS remains uncertain. We used compartmentalized neuron cultures to demonstrate that WNV spreads in both retrograde and anterograde directions via axonal transport. Transneuronal spread of WNV required axonal release of viral particles and was blocked by addition of a therapeutic neutralizing antibody. To test the physiologic significance of axonal transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
180
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 195 publications
(190 citation statements)
references
References 41 publications
(41 reference statements)
7
180
0
3
Order By: Relevance
“…Indeed, the nonneuropathogenic phenotype of some strains of WNV has been attributed to an inability to invade the CNS (12,13,27). Increasing evidence suggests that WNV entry into the CNS is a multistep process that can occur through one of several routes (17,20,(31)(32)(33)(34)(35). WNV entry into the CNS has been shown to precede disruption of the BBB and leukocyte infiltration (32,33,36,37), suggesting that WNV utilizes a direct mechanism to initially invade the CNS, such as basolateral secretion of virus particles from infected brain endothelial cells or transcytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the nonneuropathogenic phenotype of some strains of WNV has been attributed to an inability to invade the CNS (12,13,27). Increasing evidence suggests that WNV entry into the CNS is a multistep process that can occur through one of several routes (17,20,(31)(32)(33)(34)(35). WNV entry into the CNS has been shown to precede disruption of the BBB and leukocyte infiltration (32,33,36,37), suggesting that WNV utilizes a direct mechanism to initially invade the CNS, such as basolateral secretion of virus particles from infected brain endothelial cells or transcytosis.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments with HBMVECs and HBCAs were performed on cells passaged no more than 14 times. Primary cortical neurons were prepared from day 15 C57BL/6 mouse embryos as previously described (17,18). Cortical neuron experiments were performed using neurons that were cultured for 3 to 4 days in neurobasal medium containing B27 and L-glutamine (Invitrogen).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Arboviral infections typically occur in highly enervated dermis, which may lead to viral entry into the CNS through peripheral neurons. Both in vitro and in vivo studies have shown that WNV can spread along neurons via retrograde axonal microtube-mediated transport [139,140]. Indeed, intrasciatic inoculation of hamsters with WNV resulted in infection of spinal cord and acute flaccid paralysis.…”
Section: Entry Of Arboviruses Into the Cnsmentioning
confidence: 99%
“…Dans certains cas, le virus peut être inoculé directement dans la circulation sanguine court-circuitant certaines de ces étapes. Le mécanisme d'entrée du virus dans le système nerveux central n'est pas totalement compris mais plusieurs mécanismes ont été envisagés : une perméabilisation de la barrière hémato-encéphalique par les facteurs sécrétés circulants (TNF- [tumor necrosis factor], MMP9 [matrix metalloproteinase]) [10], le transport axonal rétrograde à partir des terminaisons nerveuses des neurones périphériques [11], la transcytose ou l'infection des cellules endothéliales des capillaires du cerveau [12], le transport du virus par les cellules périphériques infectées pénétrant dans le cerveau [10].…”
Section: Caractéristiques Pathologiquesunclassified
“…L'examen des tissus cérébraux montra des nodules microgliaux dispersés -notamment dans le tronc cérébral -composés de lymphocytes, histiocytes, avec une infiltration de cellules mononucléées périvasculaires, essentiellement des lymphocytes T CD8 + [13]. L'infection des neurones a été rapportée avec perte de la structure cellulaire et apoptose [11]. Les cellules mononucléées inflammatoires participeraient à l'élimination du virus dans le Les donneurs de sang, dont le sang est testé pour la présence du WNV, constituent d'excellents candidats pour la collecte d'échantillons pré-levés pendant la phase précoce de l'infection -définie par la détection de l'ARN viral en l'absence d'IgM spécifiques -avant le développement potentiel de symptômes [19].…”
Section: Encéphalites Arboviralesunclassified